Biodiesel etílico de babaçu x diesel B S1800: ensaio de opacidade da fumaça do trator agrícola variando os horários do dia - Moreti, Thaisa Calvo Fugineri [UNESP] (2015)
The use of biodiesel in agricultural tractors has environmental appeal, since it minimizes pollutant emissions and the installation of power plants that contribute to the increase of job, considering that Brazil has large territory (about 851 million hectares) and has lots of oil with potential for biodiesel production. This study aimed to discuss the main sources of raw material to produce oil, in order to obtain biodiesel, and to compare the smoke density from a tractor running on diesel B S1800 and proportions of ethyl biodiesel babassu. Among the sources for the production of oil, babassu stood out as a potential feedstock for biodiesel production. In B S1800 diesel compared with babassu biodiesel results showed significant reduction in smoke density as they increased the proportion of biodiesel use